The Drosophila DPP signal is produced by cleavage of its proprotein at evolutionary diversified furin-recognition sites. - Künnapuu, J.; Björkgren, I.; Shimmi, O. (Proceedings of the National Academy of Sciences of the United States of America, 2009)
Maturation of bone morphogenetic proteins (BMPs) requires cleavage of their precursor proteins by furin-type proprotein convertases. Here, we find that cleavage sites of the BMP2/4/decapentaplegic (DPP) subfamily have been evolutionary diversified and can be categorized into 4 different types. Cnidaria BMP2/4/DPP is considered to be a prototype containing only 1 furin site. Bilateria BMP2/4/DPP acquired an additional cleavage site with either the combination of minimal-optimal or optimal-optimal furin sites. DPPs belonging to Diptera, such as Drosophila and mosquito, and Lepidoptera of silkworm contain a third cleavage site between the 2 optimal furin sites. We studied how the 3 furin sites (FSI-III) of Drosophila DPP coordinate maturation of ligands and contribute to signals in vivo. Combining mutational analysis of furin-recognition sites and RNAi experiments, we found that the Drosophila DPP precursor is initially cleaved at an upstream furin-recognition site (FSII), with consequent cleavages at 2 furin sites (FSI and FSIII). Both Dfurin1 and Dfurin2 are involved in the processing of DPP proproteins. Biochemical and genetic analyses using cleavage mutants of DPP suggest the first cleavage at FSII to be critical and sufficient for long-range DPP signaling. Our data suggest that the Drosophila DPP precursor is cleaved in a different manner from vertebrate BMP4 even though they are functional orthologs. This indicates that the furin-cleavage sites in BMP2/4/DPP precursors are tolerant to mutations acquired through evolution and have adapted to different systems in diversified species.